Perspektif Global terhadap Upskilling and Reskilling Pendidikan Vokasi : Sebuah Studi Literatur - Ramadhan, Sany Putra; Dwiyanto, Felix Andika; Utama, Agung Bella Putra; Sutadji, Eddy (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
Abstract: The purpose of this scientific study is to find out the perspective of the upskilling and reskilling program in preparing skilled, relevant, work-ready and productive human resources in vocational education. In vocational education, most are focused on graduates who have a special expertise. The role of the teacher is the key to the successful implementation of the activities to be achieved. The right program to prepare is by upskilling and reskilling industry standards. The technique used is a literature study using the PICOC method (problem, intervention, comparison, outcome, context). The results of this literature study reveal a global perspective, application and urgency regarding industry-standard upskilling and reskilling programs for vocational education teachers.Abstrak: Tujuan dari kajian ilmiah ini untuk mengetahui prespektif program  upskilling dan reskilling dalam menyiapkan sumber daya manusia yang terampil, relevan, siap bekerja dan produktif pada Pendidikan vokasi. Pada Pendidikan vokasi, sebagian besar difokuskan dengan lulusan yang memiliki suatu keahlian khusus. Peran dari guru merupakan kunci dari keberhasilan terimplementasinya kegiatan yang akan dicapai. Program yang tepat untuk menyiapkan yakni dengan upskilling dan reskilling standar industri. Teknik yang digunakan yakni studi literature dengan metode PICOC (problem, intervention, comparation, outcome, context). Hasil dari studi literatur ini mengetahui perspektif global, penerapan dan urgensi terkait program upskilling dan reskilling berstandar industri bagi guru pendidikan vokasi.